Molecular algorithms in ovarian serous neoplasia - Flavin, Richard (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2009)
Epithelial ovarian cancer is one of the most common cancers in women and the leading cause of death from gynaecological malignancy in the western world. Approximately 205,000 cases of ovarian cancer are diagnosed worldwide each year. Serous adenocarcinomas are the commonest histotype and account for 40% -50% of malignant neoplasms. The majority of ovarian cancers present in advanced stages (III or IV) and are treated by surgery and systemic chemotherapy. Despite an initial 70-80% response rate, current therapy is frequently followed by recurrence which is often resistant to chemotherapy, as demonstrated by 5-20% long-term survivors. There is an urgent need to identify novel or poorly characterized pathways to shed more insight into the tumourigenesis of this fatal neoplasm.
Keywords: Histopathology and Morbid Anatomy, Ph.D.; Ph.D. Trinity College Dublin